The potential preventive effect of dietary phytochemicals In Vivo - Mai M. Saleh; Zeinab E. Darwish; Manal I. El Nouaem; Nesrin A. Fayed; Ghada M. Mourad; Omneya R. Ramadan (Nature Publishing Group, 2023)
Abstract Introduction Chemoprevention refers to using specific substances during oncogenesis. Curcumin and catechins are both polyphenol types of phytochemicals present in curcuma longa and green tea. The effect of curcumin is synergistic with epigallocatechin gallate, the most abundant polyphenol in tea. Aim To evaluate and compares the chemopreventive effect of both green tea and curcumin (each individually and in combination) through induction of hamster buccal pouch carcinoma. Materials and methods Squamous cell carcinoma was chemically induced in fifty Syrian golden hamsters divided into 5 groups (10 each). The first group was used as a normal control group. The second group received the carcinogenic agent only. The other three groups received green tea, curcumin, and a combination of both, respectively. Flow cytometry, immunofluorescence, and immunohistochemical assays were used to evaluate apoptosis, proliferation, and angiogenesis. ANOVA test was used to analyze the results between the study groups. Results The cells of the positive control group (B) resulted in 11.57% apoptosis. In the study groups, treatment of the cells with green tea (C), and curcumin (D) and both of them (E) showed increased apoptosis. The fluorescent image in group B showed an increase of the red fluorescence in the nucleus and cytoplasm of the squamous cell carcinoma cells while groups C, D, and E showed a decrease of the red fluorescence in the nuclei of the squamous cell carcinoma cells. The microvessel density was higher in the positive control group as compared to the treated groups. Conclusions The combination of green tea and curcumin has a significant chemopreventive effect against oral carcinogenesis.